ACUTE EFFECT OF DIFFERENT EXERCISES ORDERS IN THE MAXIMUM NUMBER OF REPETITIONS IN PROTOCOLS REALIZED WITH DIFFERENT REPETITION DURATION - Mateus Camargos Gomes; Lucas Túlio de Lacerda; Rodrigo César Ribeiro Diniz; Igor Humberto Ferreira dos Santos; Karine Silva Rodrigues; Fernando Vitor Lima (Journal of Physical Education)
ABSTRACT The objective of this study was to investigate the effect of exercise order of two exercises involving the participation of common musculature (smith machine back squat and leg curl, on the NMR, in two repetition durations. Sixteen trained male volunteers participated in this study. The protocols were performed in two exercise orders and repetition durations (self paced and 4s) in which volunteers realized their NMR in each exercise over two sets, at an intensity of 60% of 1RM, with 90 seconds between sets and 180 seconds between exercises. The ANOVA whit repeated measures were performed for comparison of the NMR and Bonferroni post hoc was applied when necessary. Regarding the self paced repetition duration, both exercises presented a higher NMR when performed as the first exercise than when performed as second. However, there was neither interaction nor main effect of the factors analyzed for the repetition duration of 4s. Therefore, it is concluded that the repetition duration is a variable capable of modifying the results found by the different orders.